Benjamin Silliman correspondence - Silliman, Benjamin, 1816-1885.
ALS from Silliman to William Laughlin, Jr. & Co., Philadelphia, Pa., relating to an order for chemical supplies.
Professor of chemistry at the Yale Scientific School.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: William Laughlin, Jr. & Co; Chemical industry -- Pennsylvania -- Philadelphia; Chemists; Educators